CHITOSAN NANOPARTICLE AS A DELIVERY SYSTEM FOR POLYPHENOLS FROM MENIRAN EXTRACT (PHYLLANTHUS NIRURI L.): FORMULATION, OPTIMIZATION, AND IMMUNOMODULATORY ACTIVITY - PRATIWI, GALIH; MARTIEN, RONNY; MURWANTI, RETNO (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aims to formulate meniran extract into polymeric nanoparticles. Better stability of active substances in formulas compared to unformulated extracts is expected to increase immunomodulatory activity. Methods: Nanoparticles were formulated using ionic gelation method with chitosan and tripolyphosphate polymers. Optimize the mixture of nanoparticles using simplex lattice design (SLD) with the help of Design-Expert (DX) software. Evaluation of particle size and potential zeta using dynamic light scattering (DLS). Interactions between components were analyzed using Fourier transform infrared spectrophotometry-attenuated total reflectance (FTIR-ATR) and morphology of the lyophilization results observed using scanning electron microscopy (SEM). Immunomodulatory tests using the latex assay method. The parameters tested included phagocytosis index, phagocytic activity, and nitric oxide secretion. Results: The optimum mixture of the formulation process was obtained in the composition of chitosan 0.270 %, extract 0.626 %, and tripolyphosphate 0.074 % with desirability value of 0.841. Optimal response with particle size 434.7±3.90 d. nm, polydispersity index 0.285±0.03 and entrapment efficiency 62.98±0.65 %. The zeta potential value in the optimum formula is 11.9±0.1 mV with a positive charge. Phagocytosis index and phagocytic activity of nanoparticles differed significantly (p<0.05) compared with unformulated extracts. Conclusion: Meniran extract was successfully formulated into polymeric nanoparticles using chitosan-tripolyphosphate polymer. The developed nanoparticles have the immunomodulatory activity that is better than unformulated extract.